Clinical aspects of arterial hypertension for the general practitioner - Vidalón-Fernández, Armando (2010)
We review basic clinical aspects of arterial hypertension (AHT). A detailed and updated definition of arterial hypertension and its correspondent classification is presented, the purpose of diagnosis, correct measurement of blood pressure and AHT identifiable causes, clinical and laboratory evaluation, vascular risk factors and target organ damage, as well as the importance of overweight/obesity and common misconceptions on AHT.